(untitled) (Research, Society and Development, 2023)
The popularization of the internet has enabled new technologies to play a more significant role in education. In this context, the study of histopathology is inserted in this process through the creation of some tools such as Virtual Microscopy (VM). The VM consists in the use of digitized histopathological slides from samples on glass slides. The overall objective of the study was to evaluate the perception of medical and dental students of a public educational institution regarding the use of MV in teaching histopathology. This is a cross-sectional study of prospective descriptive quanti-qualitative analysis. Students were invited to participate in the study and after agreeing to the Informed Consent Form, they answered an electronic questionnaire, on a Likert scale, with questions related to previous experience in other disciplines with the use of light microscopy and on the current use of Virtual Microscopy (VM), respectively. Based on the data obtained and in agreement with other studies, a preference for VM was found, with significantly higher means in almost all items. In summary, it is observed that MV is a viable tool for teaching histopathology and can be presented as a substitute or complement to the traditional method.